Trans-saccadic interactions in human parietal and occipital cortex during the retention and comparison of object orientation. (September 2016) - Dunkley, Benjamin T.; Baltaretu, Bianca; Crawford, J. Douglas
Abstract: The cortical sites for the trans-saccadic storage and integration of visual object features are unknown. Here, we used a variant of fMRI-Adaptation where subjects fixated to the left or right of a briefly presented visual grating, maintained fixation or saccaded to the opposite side, then judged whether a re-presented grating had the same or different orientation. fMRI analysis revealed trans-saccadic interactions (different > same orientation) in a visual field-insensitive cluster within right supramarginal gyrus. This cluster was located at the anterolateral pole of the parietal eye field (identified in a localizer task). We also observed gaze centered, field-specific interactions (same > different orientation) in an extrastriate cluster overlapping with putative 'V4'. Based on these data and our literature review, we conclude that these supramarginal and extrastriate areas are involved in the retention, spatial updating, and evaluation of object orientation information across saccades.